ANALISA BIAYA AKIBAT KETERLAMBATAN PROYEK STUDI KASUS PEMBANGUNAN GEDUNG ADMINISTRASI STIKES DHARMA INSAN PONTIANAK - Nafia, Ali; Syahruddin, -; Nuh, Safaruddin M. (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
Efficient step of a project is capital in the work. It is according to the specified schedule, by determining the equipment and human resources as well as the use of costs and time and efficiently in carrying out the work of a project. This paper aims to determine the amount of duration and cost after accelerating in completing project activities, according to the time in the work contract. This paper takes the project of building the Stikes Dharma Insan Pontianak Administration Building. The data needed in this study include recapitulation of project costs, list of Cost Budget Plans (RAB), list of workers' wages, number of workers in the field and timeschedhule (S Curve). The method used is by rearranging network planning, determining critical paths, calculating duration crashes, calculating crash costs, cost slopes, crashing analysis, and total cost on alternatives to adding duration of work (working hours) and adding human resources. The results obtained by accelerating (crashing) for an alternative to additional working hours, obtained a total cost of Rp. 30.059.257.120, - still experiencing a delay of 40 working days. While the alternative addition of labor is Rp. 29,080,205,120, -. completion of project activities can be completed with the time specified in the contract with a duration of 400 working daysKeywords : Crashing, critical path, working hours, labor